Workshop on the Cost of Goods Manufactured and Business Viability for SMK Tri Ratna Jakarta Students - Anggraeni, Fanny; Alexander, Nico; Rudyanto, Astrid; Putri, Ade Hanifa; Putri, Ariesta Tika Kinanti P.S.; Lasar, Hilary Flora Agustina T. (Jurnal Abdimas Sosial, Ekonomi, dan Teknologi, 2024)
The educational program at SMK Tri Ratna Jakarta focuses on cultivating entrepreneurial skills among students. They are required to develop products for sale, preparing them for entrepreneurship upon graduation. Various aspects of entrepreneurship are covered, including the calculation of Cost of Goods Manufactured and business feasibility. Accurate determination of Cost of Goods Manufactured is crucial for predicting potential profits, as errors in this process can lead to financial losses. Business feasibility is assessed through metrics such as payback period and Break Even Point. Recognizing the lack of information on these topics among students, the author initiated training sessions on Cost of Goods Manufactured calculation and business feasibility at SMK Tri Ratna Jakarta. The training sessions employed lecture and discussion methods to impart knowledge. The outcome of these sessions was enhanced understanding among students regarding the components of Cost of Goods Manufactured and methods for determining business feasibility using two different approaches. Students actively engaged in the training, demonstrating enthusiasm by asking numerous questions about Cost of Goods Manufactured calculations and business feasibility assessments for their products.